Trichoderma spp. communities in paddy fields at Pasir Mas, Kelantan - Nor Aqilah Mat Resad (2016)
The Trichoderma spp. is the fungus that can used as biocontrol agent to subsitutes the agrochemical is harmful for the environment. Trichoderma spp. can be found at agricultural land or rhizopheres land. The aim of this study was to isolate and identify the Trichoderma spp.at agricultural land which was paddy cultivated soils at Pasir Mas at Pasir Mas, Kelantan.For the effectiveness as biocontrol agent of the isolated Trichoderma spp. from the paddy soil at Pasir Mas, the fungus was tested as its’s antagonistic activity aganist Ganoderma spp.( a causal pathogen for basal stem rot diseases in oil palm).Through the soil serial dilution which were from l0⁻ᶟ, 10⁻⁴, and l0⁻⁵ a total of four isolates of Trichoderma colonies were able to identiﬁed. Two different species of Trichoderma spp. was able to identify which were Trichoderma harzianum and Trichoderma koningii. Out of the four isolates the morphological and anatomical of Trichoderma spp. was identify through naked eyes or observation under light microscope. The morphological characteristics observed as similar with Trichoderma’s physical characterisation show as colony colour or appearance, growth rate while, for anatomical or micro morphological features observed as the shape of phialide, conidiophores and the shape of phialidiaspores. Out of four isolates colony, three colonies were similar characteristics with Trichoderma koningii which later on coded as TKPPAI, TKPPB2 and TKPPB3. The antagonistic activity of Trichoderma spp. was tested against the pathogenic fungus which were Ganoderma boninense strain (UPMOOI) and Ganoderma sp. Antagonistic data showed that all four isolates THPPA4, TKPPAI, TKPPB2 and TKPPB3 were inhibit the growth of the pathogenic fungi of G.boninense (UPMOOI) and Ganoderma sp. While, the percentage of inhibition (PIRG) of radial growth was different according to the isolated species or strain of Trichoderma which coded as THPPA4, TKPPAl, TKPPB2 and TKPPB3. Among the four strains (TKPPA1, TKPPB2 and TKPPB3) of Trichoderma koningii of the highest antagonistic activity to 81.00% was found in TKPPB3 against Ganoderma sp. on the hand, the species of Trichoderma harzianum strain THPPT4 showed 60.86% antagonistic activity against G. boninense (UPMOOI). It can be concluded that, all isolated strain have the good antagonistic activity against either Ganoderma boninense (UPMOOI) or Ganoderma sp. but the strength on effective antagonistic depend on the pathogenic species and biocontrol relationship.